A model for integrating strategic planning and competence-based curriculum design in establishing a public health programme: the UNC Charlotte experience - Harver Andrew; Thompson Michael E; Eure Marquis (BMC, 2009)
Abstract Introduction The University of North Carolina at Charlotte, a doctoral/research-intensive university, is the largest institution of higher education in the Charlotte region. The university currently offers 18 doctoral, 62 master's and 90 baccalaureate programmes. Fall 2008 enrolment exceeded 23 300 students, including more than 4900 graduate students. The university's Department of Health Behavior and Administration was established on 1 July 2002 as part of a transformed College of Health & Human Services. Case description In 2003, the Department initiated a series of stakeholder activities as part of its strategic planning and programmatic realignment efforts. The Department followed an empirically derived top-down/bottom-up strategic planning process that fostered community engagement and coordination of efforts across institutional levels. This process culminated in a vision to transform the unit into a Council on Education for Public Health accredited programme in public health and, eventually, an accredited school of public health. To date, the Department has revised its Master of Science in health promotion into an Master of Science in Public Health programme, renamed itself the Department of Public Health Sciences, launched a Bachelor of Science in Public Health major, laid plans for a doctoral programme, and received accreditation from the Council on Education for Public Health as a public health programme. Furthermore, the campus has endorsed the programme's growth into a school of public health as one of its priorities. Discussion and Evaluation It is only through this rigorous and cyclical process of determining what society needs, designing a curriculum specifically to prepare graduates to meet those needs, ensuring that those graduates meet those needs, and reassessing society's needs that we can continue to advance the profession and ensure the public's health. Community stakeholders should be active contributors to programme innovation. Lessons learnt from this process include: being connected to your community and knowing its needs, being responsive to your community, remembering that process is as important as product, and preparing for success. Conclusion The efforts reported here can be informative to other institutions by exemplifying an integrated top-down/bottom-up process of strategic planning that ensures that a department's degree programmes meet current needs and that students graduate with the competences to address those needs.